POTENTIAL OF ENTOMOPATHOGENIC NEMATODES FOR CONTROL OF THE ERVA-MATE PEST HEDYPATHES BETULINUS (KLUG, 1825) (COLEOPTERA: CERAMBYCIDAE) - Alves, Viviane Sandra; Angeli Alves, Luis Francisco; Fanti, André Luis Pereira; Alves, Marilia Souza (Floresta, 2017)
The intensive exploitation of “erva mate” (Ilex paraguariensis St. Hil.) (Aquifoliaceae) has favored the emergence of pests, including Hedypathes betulinus. We evaluated 18 isolates of entomopathogenic nematodes in the Steinernema and Heterorhabditis genera for control of H. betulinus adults, and tested nematode in-vivo replication capacity in Galleria mellonella L. (Lepidoptera: Pyralidae) larvae. We also evaluated the effect of adjuvants for foliar application, and the efficiency of nematode isolates selected in erva mate seedlings in the greenhouse via application to soil and plant shoots. The PI and CB40 isolates showed the hgh virulence (92.5% insect mortality by both). The PI isolate showed low productivity in G. mellonella larvae, thus only CB40 was used in subsequent tests. Only emulsified vegetable oil adjuvant was compatible with nematodes. Soil application of nematodes proved ineffective; however, shoot application on erva mate seedlings showed significant mortality (82.5%) after exposure to the CB40 isolate without adjuvant.